Perbandingan Metode CBIA dan FGD dalam Peningkatan Pengetahuan dan Ketepatan Caregiver dalam Upaya Swamedikasi Demam pada Anak - Lathifah, Marianti Avi; Susanti, Susanti; Ilham, Much; Wibowo, Aji (Pharmaceutical Sciences and Research, 2015)
Self medications which are ofted applied to children are including coughs, colds, flu, and nasal congestion (17.2%), fever (15%), headache (14%), diarrhea and abdominal pain (9%). The results from previous studies showed only 0.4% caregiver of 4-6 years old children in Banyumas Regency did correctly in children’s fever self medication. Aim of this study is to determine the influence of Community Based Interactive Approach (CBIA) and Focus Group Discussion (FGD) methods for improving knowledge and correctness of caregivers in children’s fever self medication with type of research of quasi experimental design with a control group of non random pretest posttest. Results of Wilcoxon test showed that there were significant differences of knowledge statistically before and after treatment using the FGD and CBIA methods with significancy values in FGD group of 0.000 (p < 0.05) and in CBIA group of 0.002 (p < 0.05), while for correctness before and after treatment with FGD and CBIA methods, there were no statistically significant difference in significancy values of correctness for FGD group of 1,000 (p> 0.05) and for the CBIA group of 1,000 (p> 0.05). Results of Mann-Whitney test showed that the obtained significancy value was 0.012 (p <0.05), it can be concluded that there were significant differences between FGD with CBIA groups. The difference of Mean scores in FGD group (2.45) were greater than the CBIA group (0.96), so that the FGD method was better in improving the knowledge compared with CBIA method even though they both gave some improvements.. Fisher’s Exact test results showed that the ​obtained significancy value was 1,000. According to these statistical analysis results, it can be concluded that based on statistical calculatios, there is no significant difference between FGD and CBIA methods in improving the correctness of children’s fever self medication.